Citizens Inclusion in the Political Decision-Making Process as a Determinant of Sustainable Development Implementation - Kaszkur, Alina; Kapsa, Izabela (European Journal of Sustainable Development, 2019)
All efforts to involve the society in the affairs of local communities are an important aspect of the implementation of the principle of sustainable development. Citizen’s involvement in decision making processes not only positively correlates with their sense of action, but also affects the quality of decisions made by public authorities which gain the opportunity to learn more about the needs and expectations of citizens. The best conditions for the implementation the principle of sustainable development, basing on the dialogue with citizens, are on local level – in the cities. Moreover, using new information and communication technologies opens a number of possibilities to even more fully activation of local communities. As a consequence, the residents have greater impact on the quality of political decisions, that take into account their needs and expectations, it is also a chance to improve the quality of their life. The main research goal of the article is to answer the question – what characterizes sustainable development of the city and how the use of information and communication technologies by public authorities may affect a more complete implementation of the principle of sustainable development. The research method is an analysis of the documents and source materials. Keywords: civic engagement, e-participation, information and communication technologies, local authorities, sustainable development of the cities